2022
DOI: 10.1111/phpp.12808
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and common ultraviolet filter usage of sunscreens purchased online: Cross‐cultural analysis across 5 continents

Abstract: Background: A wide range of sunscreen products are available globally. Designed to meet various customer needs, they differ in formulations type, textures, ingredients, ultraviolet (UV) protection capabilities, and other properties. Knowing the factors influencing the purchase of sunscreens and the UV filters commonly used in each global region would be beneficial for dermatologists, consumers, and regulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A recent study that surveyed common UV filters used in sunscreens purchased online across five continents found that 31% of sunscreens in Europe were labelled 'reef safe', and approximately one-third of Europeans were choosing these sunscreens. 8 Studies have demonstrated that nanoparticles of inorganic UV filters like titanium dioxide and zinc oxide can also have toxic effects on marine microalgae and zooplankton. 2,5 Only 15 of the 60 permitted UV filters worldwide have been tested for toxic effects on the marine environment, and thus, there is limited safety evidence for several UV filters.…”
Section: Reef Safe Sunscreens: a Call To Actionmentioning
confidence: 99%
“…A recent study that surveyed common UV filters used in sunscreens purchased online across five continents found that 31% of sunscreens in Europe were labelled 'reef safe', and approximately one-third of Europeans were choosing these sunscreens. 8 Studies have demonstrated that nanoparticles of inorganic UV filters like titanium dioxide and zinc oxide can also have toxic effects on marine microalgae and zooplankton. 2,5 Only 15 of the 60 permitted UV filters worldwide have been tested for toxic effects on the marine environment, and thus, there is limited safety evidence for several UV filters.…”
Section: Reef Safe Sunscreens: a Call To Actionmentioning
confidence: 99%